Pengaruh asimetri informasi, leverage, kualitas akrual, dan profitabilitas terhadap kualitas laba (studi pada perusahaan manufaktur yang terdaftar di bei 2010-2011) - Karolus Timotius; Vince Ratnawati; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The aimed of this research to analyzed the effect of information asymmetry, leverage, accrual quality, and profitability to the quality of earnings. The population of this study is companies listed on the Indonesia Stock Exchange (IDX) in 2010 to 2011. Samples was determined by purposive sampling method. There are 60 manufacturing companies. Analysis of the data was use as multiple regression analysis. The result that information asymmetry of does not affect on the quality of earnings but leverage, accrual quality, and profitability of a significant effect the quality of earnings. Based on the research, we can suggested: for the next research you should use another variables such as systematic risk, liquidity, investment opportunity set, and a chance to grow and add the longer period of observation.Keywords: Information Asymmetry, Leverage, Accrual Quality, Profitability, Quality of Earnings